Trends of Adverse Events Following Immunization (AEFI) Reports of Human Papillomavirus Vaccine in the Valencian Community—Spain (2008–2018) - Cecilia M. Egoavil; José Tuells; Juan José Carreras; Emilia Montagud; Eliseo Pastor-Villalba; Pablo Caballero; Andreu Nolasco (Vaccines, 2020)
Vaccine safety surveillance is essential in vaccination programs. We accomplished a descriptive study of surveillance AEFI-reporting rate in human papillomavirus (HPV) vaccine administered in the Valencian Community, Spain. Data were obtained from Spanish Pharmacovigilance Adverse Reactions Data (FEDRA). Reporting rates were calculated using local net doses distributed as the denominator. Trends were assessed using joinpoint regression with annual percent change (APC) reported. The AEFI-reports decreased between 2008 and 2018 in two periods, a fast decreasing rate from 2009 to 2011 (from 192.2 to 24.93 per 100000 doses; APC, −54.9%; 95%CI [−75.2; −17.7]), followed by a stable trend (−13% APC, 95%CI [−26.1; 2.4]). For the age group analysis, only the group aged 14−15 years old followed the same trend with -58.4% (95%CI [−73.9; −33.8]) APC during 2008−2011, and −8.8% (95%CI [−27.7; 15]) APC during 2011-2018. The majority of the reports (73.82%) were nonserious, involving reactions at or near the vaccination site, headache, and dizziness events. No death was reported. AEFI-reporting rates for HPV immunization in the Valencian Community have decreased considerably with two trend periods observed for girls aged 14−15 years old. Currently, the AEFI reporting rate shows a decreasing trend, perhaps following the Weber effect, and it could also be affected by media attention and coverage.